Sucesso reprodutivo de Fernseea itatiaiae no contexto comunitário das interações planta-polinizador - Rigotto, Sarah Mendonça (2024)
Animal pollinators are of great importance for plant reproduction, as they contribute to seed production and promote outcrossing between individuals, leading to genetic variability. In communities, shared pollinators connect plant species, potentially influencing each other through indirect effects, such as facilitation or competition for visits from animals like hummingbirds. In this context, an important resource for hummingbirds is the Bromeliaceae family. Fernseea itatiaiae is an ornithophilous bromeliad with a restricted distribution to the high-altitude fields of Itatiaia National Park (southeast Brazil), assessed as endangered (EN). We investigated the role of plant-hummingbird interaction networks in maintaining the ornithophilous community of high-altitude fields and, consequently, the conservation of Fernseea itatiaiae. To achieve this, we measured the flowering phenology of ornithophilous species along three trails in the Itatiaia National Park. Subsequently, we assessed the overlap in hummingbird use among species in the plant-pollinator network and evaluated the importance of species in the network using species-level metrics (d', species strength, closeness, and weighted closeness). To assess the reproductive system and pollination success in F. itatiaiae, we conducted controlled pollination treatments and germination tests of the seeds generated. Network results showed that species with stronger interactions with shared hummingbirds in the community were Fuchsia regia, F. itatiaiae, and Buddleja speciosissima. When evaluating the species metrics in the network, the obtained values are not sufficient to determine how close they are and which nodes play a central and influential role. However, by associating F. itatiaiae's dependence on pollinators for reproduction with network outcomes, we see its importance in the community and its role as a mediator of pollinator-sharing processes. Additionally, experiments showed that the presence of ornithophilous neighbors and other ornithophilous flowers in the community does not significantly influence F. itatiaiae's pollination, and its reproductive success depends directly on the presence of hummingbirds. Our results highlight the importance of F. itatiaiae in the ornithophilous community in the high-altitude fields of Itatiaia National Park. In addition to contributing to the maintenance of plant species in the environment, it also contributes to the persistence of hummingbird species responsible for pollinating other ornithophilous species.